RISKS AND VULNERABILITIES OF CHILDREN IN ZAMBIA: MOOTING RESPONSIVE SOCIAL PROTECTION INTERVENTIONS - Moonga, Fred; Green, Sulina (Social Work/Maatskaplike Werk, 2016)
Social protection has not only assumed another dimension characterised by income transfers, but has also aroused intense interest among researchers, policy makers and practitioners. In spite of this development, and its evident effectiveness in averting poverty, risks and vulnerabilities, interventions for children have been disappointingly limited. This study attempts to review the literature on the risks and vulnerabilities that affect children in Zambia. It argues that risks and vulnerabilities vary according to age, gender and residence, among other things. Therefore it proposes a design of social protection interventions that would take into account the multiplicity of vulnerabilities in Zambia.